2013
DOI: 10.1037/a0029531
|View full text |Cite
|
Sign up to set email alerts
|

Mind-sets matter: A meta-analytic review of implicit theories and self-regulation.

Abstract: This review builds on self-control theory (Carver & Scheier, 1998) to develop a theoretical framework for investigating associations of implicit theories with self-regulation. This framework conceptualizes self-regulation in terms of three crucial processes: goal setting, goal operating and goal monitoring. In this meta-analysis, we included articles that reported a quantifiable assessment of implicit theories and at least one self-regulatory process or outcome. Using a random effects approach, meta-analytic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
903
11
36

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 971 publications
(1,016 citation statements)
references
References 199 publications
(422 reference statements)
66
903
11
36
Order By: Relevance
“…Importantly, the self-regulatory processes associated with growth mindset are positively associated with goal achievement. Growth mindset itself was therefore shown to be associated with a higher likelihood of achieving one's goals; even though, the results of the meta-analysis suggest that the association is weak (Burnette et al, 2013).While Burnette et al (2013) showed the association between implicit theories and achievement, some research (e.g., Blackwell, Trzesniewski, & Dweck, 2007; see also Yeager et al, 2014) suggests that people with growth and fixed mindset may not differ in their baseline abilities and the difference appears only when encountering adversities or challenging situations. For example, students with growth and fixed mindset may not differ in their mathematics grades before entering junior high school, but the transition to high school poses a significant challenge to which students with growth mindset might adapt better.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Importantly, the self-regulatory processes associated with growth mindset are positively associated with goal achievement. Growth mindset itself was therefore shown to be associated with a higher likelihood of achieving one's goals; even though, the results of the meta-analysis suggest that the association is weak (Burnette et al, 2013).While Burnette et al (2013) showed the association between implicit theories and achievement, some research (e.g., Blackwell, Trzesniewski, & Dweck, 2007; see also Yeager et al, 2014) suggests that people with growth and fixed mindset may not differ in their baseline abilities and the difference appears only when encountering adversities or challenging situations. For example, students with growth and fixed mindset may not differ in their mathematics grades before entering junior high school, but the transition to high school poses a significant challenge to which students with growth mindset might adapt better.…”
mentioning
confidence: 87%
“…These two views are labeled as a fixed mindset and growth mindset, respectively (Dweck, 2012;Dweck & Leggett, 1988;Molden & Dweck, 2006). A recent metaanalysis showed that implicit theories about intelligence are associated with various aspects of self-regulation (Burnette, O'Boyle, VanEpps, Pollack, & Finkel, 2013). People with growth mindset tend to set learning goals rather than performance goals, they tend to adopt strategies focused on mastery rather than helpless-oriented strategies, and when monitoring their goal achievement, they tend to focus on future expectations of success rather than negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been shown to be associated with other constructs including academic motivation (Ommundsen et al 2005), cognitive engagement (Dupeyrat and Mariné 2005), learning and achievement goals (Blackwell et al 2007;Dinger and Dickhäuser 2013), epistemic beliefs and goal orientations (Chen and Pajares 2010), selfefficacy (Chen and Pajares 2010;Davis et al 2011), and self-regulated learning (Burnette et al 2013;Greene et al 2010). While clearly an important framework, an alternative position on implicit theories exists with respect to the 'prototypical' nature of intelligence.…”
Section: Implicit Theories Of the Prototypical Nature Of Intelligencementioning
confidence: 99%
“…However, although effort beliefs played a prominent role in Dweck's (1999) monograph introducing the self-theories meaning system, empirical research mostly focussed on the derivation of relationships between implicit theories, and goal setting behaviour and self-regulation of learning (Burnette et al, 2012). Given that the large majority of empirical studies based on the self-theories framework have not explicitly conceptualized effort belief constructs, we assert that the full potential of self-theoretical frameworks is yet to be achieved.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Studies that do leave out students' beliefs as mediators of the relationships between implicit theories and achievement goals, be it effort beliefs or epistemological beliefs as in the Chen and Pajares (2010) study, typically find no more than very weak direct relationships between implicit theories and achievement goals. In their very recent metaanalysis of 113 empirical studies on implicit theories, Burnette, O'Boyle, VanEpps, Pollack, and Finkel (2012) conclude that 'incremental theories correlate negatively with performance goals and positively with learning goals, although these correlations are small to moderate in magnitude' (p. 19), correlations being -. 15 and .19, respectively.…”
Section: Introductionmentioning
confidence: 99%